The Role of the Quran in Shaping Modern Morality: A Contemporary Review: Peran Al-Quran dalam Membentuk Moralitas Modern: Sebuah Tinjauan Kontemporer - Ushama Ushama; Mohammad Irfan Farraz Haecal; Yusuff Yusuff (Senarai: Journal of Islamic Heritage and Civilization, 2025)
Contemporary society faces a variety of complex ethical and moral issues arising from powerful social forces such as terrorism, globalization, materialism, consumerism, and rapid technological and social structural changes. The moral teachings of the Quran remain crucial in addressing these issues and providing relevant solutions to modern dilemmas. This study explores the Quran as a vital source of ethical and moral guidance for humanity in contemporary society. Content analysis is employed to identify key Quranic verses that have implications for ethical and moral behavior in modern society. Keywords such as “justice,” “compassion and mercy,” “honesty and truth,” “stewardship,” “humility and simplicity,” and “generosity and charity” are used to identify relevant verses. A detailed examination and analysis of the findings reveal that the Quran emphasizes the importance of several timeless principles such as justice, compassion, honesty, stewardship, humility, and generosity. These findings also indicate that the Quran offers a comprehensive framework for ethical behavior relevant to addressing issues of injustice, dishonesty, environmental degradation, and social inequality in contemporary society.